The Adverse Effect of COVID Pandemic on the Care of Patients With Kidney Diseases in India - Narayan Prasad (Kidney International Reports, 2020)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has affected the care of patients with noncommunicable diseases, including those suffering from kidney-related ailments. Many parts of the world, including India, adopted lockdown to curb community transmission of disease. The lockdown affected transportation, access to health care facilities, and availability of medicines and consumables as well as outpatient and inpatient services. We aimed to analyze the effect of lockdown imposed due to the COVID-19 pandemic on the care of patients with kidney diseases in India. Methods: We surveyed 19 major hospitals (8 in the public and 11 in the private sector) to determine the effect of lockdown on the care of patients with kidney disease, including those on dialysis after the first 3 weeks of lockdown. Results: The total number of dialysis patients in these centers came down from 2517 to 2404. Approximately 710 (28.2%) patients missed 1 or more dialysis sessions, 69 (2.74%) required emergency dialysis sessions, 104 (4.13%) stopped reporting for dialysis, and 9 (0.36%) were confirmed to have died. Outpatient attendance in the surveyed hospital came down by 92.3%, and inpatient service reduced by 61%. Tele-consultation was started but was accessed by only a small number of patients. Conclusion: Lack of preparedness before lockdown resulted in an interruption in health care services and posed an immediate adverse effect on the outcome of dialysis patients and patients with kidney disease in India. The long-term impact on the health of patients with less severe forms of kidney disease remains unknown.